Pendampingan Bisnis Dan Perizinan Berusaha Terintegrasi Secara Elektronik Berbasis Risiko Melalui Online Single Submission (OSS) Bagi Wirausaha Pemula Aceh - Rahmat Arfan; Mirnawati Mirnawati; Ricky Ariansyah; Indra Akbar; Desy Puspita; Zahriatul Aini (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
This Community service program was initiated by Polytechnic Kutaraja and collaboration with PLUT UMKM Banda Aceh a as learning facility and program socialization in a product, packaging, and business permit. The best Business assistant not only explains the product but also explain business permits, packaging, and other more about way to make an effective micro business, it is much needed late because people are increasingly aware of a business permit as facility consumption security and the way they choose product base on look likes. Besides that, this program also explains packaging as easy marketing method and also informs about what the product contains to customers and how they chose the product because the product is attractive.Then this program added information about how to publish their permit number (NIB) as business identity and how easy to publish this NIB where on this program they trained and guided on publishing their business permit.Lastly hoping to this program will be continued and can schedule every year to help micro business to get information about the business permit, good products, and attractive packaging.